Importance applications mobile agent technology for virtual e-learning environment: Proposed model - Basha, Ahmed Dheyaa Basha; Mnaathr, Satar Habib; Alminshid, Khalid Abdulrazzaq Abdulnabi; Umar, Irfan Naufal (Enhanced Research Publications, 2013)
In current era Mobile Agent (MA) technology is engaging so much attention as an urgent request. Many applications for Mobile Agent goes via the web like commercial transaction, sale room, and job finder, etc.. Mobile Agent Technology may contribute in solving many problems for several companies because Mobile agent technology is a very appealing solution for this kind of problem. Of later E-learning attracts most recent technologies seeks to model and to display the most perfect and suitable solution to cover the majority of the processes needed in its web_based virtual environment. Mobile Agent occupied of e-learning to facilitate the mechanism with the learning environment among the diverse parties. This study highlights some of the important problems that appear in the web_based virtual learning environment (VLE), and showed a model with one of the recent and the main technologies as a solve for the Mobile Agent’ problems.This study presents the interactive and collaborative, and vital role of the Mobile Agent in connecting intellectual efforts between students and instructors working in a secure VLE bearing in mind agents’ roles, tasks and interactions in the analysis.